Rancang Bangun Aplikasi Game Edukasi Berbasis Android Belajar Mengenal Huruf Hijaiyah - Fahruji; Dede Supiyan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The advancement of science and technology has continuously increased in line with various human needs. In addition, the impact of the Covid-19 pandemic has resulted in the number of smartphones connected to the network in Indonesia increasing to 370.1 million in January 2022. The problem that arises is children who are lazy to study, especially learning to recite the Koran and how to make educative learning methods for children to know hijaiyah letters or learn to recite the Koran. Data collection techniques used in are: interviews, observation, and literature study. MDLC (Multimedia Development Life Cycle) is a system development method that is suitable for developing multimedia systems because of the use of computers to represent and combine text, sound, images, and animation in an application system. By making this application it can help in good interaction between users because of the menu feature to play games together. An educational application game was created that provides a learning experience as well as playing so that children are more diligent in learning hijaiyah letters or the Al-Qur'an. The display design of the application is designed to be attractive to give new impetus for children to recognize hijaiyah letters, so they don't get bored and lazy when learning to recognize hijaiyah letters.